In vitro characterization of design and compressive properties of 3D-biofabricated/decellularized hybrid grafts for tracheal tissue engineering. (June 2016) - Johnson, Christopher; Sheshadri, Priyanka; Ketchum, Jessica M.; Narayanan, Lokesh K.; Weinberger, Paul M.; Shirwaiker, Rohan A.
Abstract: Infection or damage to the trachea, a thin walled and cartilage reinforced conduit that connects the pharynx and larynx to the lungs, leads to serious respiratory medical conditions which can often prove fatal. Current clinical strategies for complex tracheal reconstruction are of limited availability and efficacy, but tissue engineering and regenerative medicine approaches may provide viable alternatives. In this study, we have developed a new "hybrid graft" approach that utilizes decellularized tracheal tissue along with a resorbable polymer scaffold, and holds promise for potential clinical applications. First, we evaluated the effect of our decellularization process on the compression properties of porcine tracheal segments, and noted approximately 63% decrease in resistance to compression following decellularization. Next we developed four C-shape scaffold designs by varying the base geometry and thickness, and fabricated polycaprolactone scaffolds using a combination of 3D-Bioplotting and thermally-assisted forming. All scaffolds designs were evaluated in vitro under three different environmental testing conditions to determine the design that offered the best resistance to compression. These were further studied to determine the effect of gamma radiation sterilization and cyclic compression loading. Finally, hybrid grafts were developed by securing these optimal design scaffolds to decellularized tracheal segments and evaluated in vitro under physiological testing conditions. Results show that the resistance to compression offered by the hybrid grafts created using gamma radiation sterilized scaffolds was comparable to that of fresh tracheal segments. Given that current clinical attempts at tracheal transplantation using decellularized tissue have been fraught with luminal collapse and complications, our data support the possibility that future embodiments using a hybrid graft approach may reduce the need for intraluminal stenting in tracheal transplant recipients. Graphical abstract: